Information Systems Research for Smart Sustainable Mobility: A Framework and Call for Action - Ketter, Wolfgang; Schroer, Karsten; Valogianni, Konstantina (Informs, 2023)
Transportation is a backbone of modern globalized societies. It also causes approximately one third of all European Union and U.S. greenhouse gas emissions, represents a major health hazard for global populations, and poses significant economic costs (e.g., due to traffic congestion). However, rapid innovation in vehicle technology, mobile connectivity, computing hardware, and artificial intelligence–powered information systems heralds a deep socio-technical transformation of the sector. The emergence of connected, autonomous, shared, and electric vehicle technology has created a digital layer that resides on top of the traditional physical mobility system. The resulting layered modular architecture is similar to that seen in other cyber-physical systems. Yet, it also comes with several characteristics and challenges that are unique to the domain of mobility and require entirely new solution approaches. Although other management and domain-specific research disciplines have started to embrace the new opportunities for research resulting from this deep structural change, the information systems (IS) community’s involvement in smart mobility research has been marginal. Yet, we argue that our field’s uniquely multidisciplinary, data-driven, and socio-technical research lens puts it in a strong position to address many of the large-scale societal challenges encountered in the mobility sector. Therefore, we make the case for IS research to play an active role in delivering a smart sustainable mobility ecosystem that is beneficial to users, mobility providers and the environment. We contribute a research framework to direct IS research efforts while providing a shared understanding of the smart sustainable mobility domain. We also present seven IS research opportunities along the dimensions of this framework and propose concrete angles of attack which we hope will spur an impactful and structured research agenda in the area.
Keywords: CASE vehicles;Smart sustainability mobility;Digital platform;IS for Social Good;Green IS; CASE vehicles; Smart sustainability mobility; Digital platform; IS for Social Good; Green IS; 33 Ciencias Tecnológicas; ODS 11 - Ciudades y comunidades sostenibles; ODS 13 - Acción por el clima; ODS 16 - Paz, justicia e instituciones sólidas